Opportunities and challenges of artificial intelligence in healthcare - Iliashenko, Oksana; Bikkulova, Zilia; Dubgorn, Alissa (E3S web of conferences, 2019)
In this article, an overview of existing cases of usage of artificial intelligence (hereinafter AI) in healthcare is made, and opportunities of AI technologies and challenges one may face while embedding and using them are studied. In literature, there are several definitions of AI given in different dictionaries and studies. These definitions are mentioned in the article. In the framework of this article, AI is understood as the capability of a machine to imitate intelligent human behavior. The object of the research is AI in healthcare. The goal of the research is to make a representation of current usage of AI in healthcare. The goal is concretized by the following tasks: to classify AI systems used in healthcare and to make a world map of top AI startups in this field. The method used for the research is statistical observation by studying of sources about current projects in AI market.